Is There a Role for Urodynamic Study in Women with Urinary Incontinence? - Ayati, Elnaz; Ghanbari, Zinat; Ayati, Mohsen; Amini, Erfan; Deldar Pesikhani, Maryam (Urology Journal, 2016)
Purpose: To compare clinical and urodynamic study (UDS) findings in Iranian women with mixed or stress UI (Urinary Incontinence). Materials and methods: A total of 132 patients with either stress or mixed type of UI were enrolled. After accurate examination, data regarding age, parity, mode of delivery and menopausal state were recorded. Furthermore the presence and severity of UI was evaluated with empty bladder supine stress test (ESST) and cough test in supine and standing positions in all patients. Eligible cases underwent UDS evaluation by an expert urologist using a standardized protocol. Results: Stress and mixed UI were found in 33 (25%) and 99 (75%) patients respectively. By considering clinical evaluation as gold standard, sensitivity, specificity, positive and negative predictive value of urodynamic study were 83.4%, 30.4%, 43.4% and 80% for detecting stress UI and 96.1%, 35.6%, 34.7%, 96.2% for detecting mixed UI respectively. No correlation was noted between ESST or cough test results and Valsalva leak point pressure (VLPP) values in patients with stress UI, however ESST was correlated with VLPP values in patients with mixed UI. Conclusion: Despite a relatively high sensitivity, the specificity was low and urodynamic evaluation seems to be of limited value in the assessment of UI in female patients.